Relationship Between 24-Hour Urine and Serum Parameters in Patients with Nephrolithiasis - Erdamar, Hüsamettin; Sancak, Banu; Bukan, Neslihan; Paşaoğlu, Hatice (Fırat University, 2007)
Objective: Nephrolithiasis is a common disease, whereas the mechanisms by which stones develop in the kidney are poorly understood. While high levels of oxalate, uric acid, calcium, and phosphate in the urine increase the formation of nephrolithiasis, increased urinary excretion of citrate, magnesium, albumin and alkali urine decrease this process. In this study, we aimed to identify the possible relationship between some serum and 24- hour urinary parameters in patients with nephrolithiasis. Materials and Methods: Two hundreds thirty-one patients with nephrolithiasis (aged 18-65 years; 143 men, 88 women) were retrospectively examined in this study. Results: Significant correlations observed between urine and serum levels of creatinine with urine and serum levels of uric acid [r= 0.70, (p

Amaç: Nefrolitiazis yaygın bir hastalık olmasına rağmen, böbrekteki taş oluşum mekanizması tam olarak anlaşılamamıştır. İdrarda yüksek konsantrasyonda oksalat, ürik asit, kalsiyum ve fosfor bulunması nefrolitiazis oluşma riskini arttırırken; sitrat, magnezyum, albumin düzeylerinin yüksekliği ve idrarın alkali olması ise bu riski azaltmaktadır. Bu çalışmada nefrolitiasizli hastalarda serum ve 24 saatlik idrar analizi sonucu elde edilen parametreler arasındaki muhtemel ilişkiyi tespit etmeyi amaçladık. Gereç ve Yöntem: 231 adet nefrolitiazisli hasta (18-65 yaşları arasında; 143 erkek, 88 kadın)retrospektif olarak incelendi. Bulgular: İdrar ve serum kreatinin değerleri ile idrar ve serum ürik asit değerleri arasında [sırasıyla r= 0.70, (p
Nefrolitiazisli Hastalarda 24 Saatlik İdrar ve Serum Parametreleri Arasında İlişki